Clinical resolution in diagnosis of leukoplastic lesion associated with oral dysplasia: case report (Research, Society and Development, 2023)
The objective of the present study is to report a clinical case that emphasizes the diagnosis of mild epithelial dysplasia located in the unilateral region of the buccal mucosa. Patient, 49 years old, female, pheoderma, attended the dental clinic of the Nilton Lins University, referring a dental fracture as the main reason for the consultation. The intraoral clinical examination revealed a unilateral lesion in the buccal mucosa with plaque characteristics and whitish coloration. Initially, it was decided to perform an excisional biopsy of the lesion with a diagnostic hypothesis of lichen planus. The extracted pieces were sent to the Department of Pathology and Legal Medicine of the Federal University of Amazonas School of Medicine for confirmation of the diagnostic hypothesis, confirmed by the report as mild epithelial dysplasia. Subsequently, the patient was referred to perform the other dental procedures that were later scheduled and is under follow-up, with no complaints or adverse complications. Therefore, given the clinical resolution presented, the differential diagnosis was essential, enabling a satisfactory clinical conduct.